Evaluation of antitumor activity of a TGF-beta receptor I inhibitor (SD-208) on human colon adenocarcinoma - Akbari, Abolfazl (BioMed Central, 2014)
BACKGROUND: Transforming growth factor-β (TGF-β) pathway is involved in primary tumor progression and in promoting metastasis in a considerable proportion of human cancers such as colorectal cancer (CRC). Therefore, blockage of TGF-β pathway signaling via an inhibitor could be a valuable tool in CRC treatment. METHODS: To evaluate the efficacy of systemic targeting of the TGF-β pathway for therapeutic effects on CRC, we investigated the effects of a TGβRI (TGF-β receptor 1) or TβRI kinase inhibitor, SD-208, on SW-48, colon adenocarcinoma cells. In this work, in vitro cell proliferation was studied by methyl thiazolyl tetrazolium (MTT) and bromo-2′-deoxyuridine (BrdU) assays. Also, the histopathological and immunohistochemical evaluations were conducted by hematoxylin and eosin, and Ki-67 and CD34 markers were stained, respectively. RESULTS: Our results showed no significant reduction in cell proliferation and vessel formation (170 ± 70 and 165 ± 70, P > 0.05) in treated SW-48 cells with SD-208 compared to controls. CONCLUSION: Our data suggested that SD-208 could not significantly reduce tumor growth and angiogenesis in human colorectal cancer model at least using SW-48 cells.